Development of Bouillon cubes from bangos (Chanos Chanos, Forskal) - Jardenil, June Jasmin A.
Fish powder was produced using the wet reduction method with 1:2 alcohol to water solvent. Filleted and whole bangos were used for the fish powder production and dried at 71°C, 79°C and 85°C. The optimum drying temperature was found to be at 85°C for 5 1/2 to 6 hours of drying. The microbial load of the powders were determined using the Total Plate Count and the Yeast and Mold Count. Results showed that filleted bangos dried at 79°C and 85°C had the least number of growth, whereas whole bangos dried at 79°C and 85°C came second. The powders dried at 71°C showed the highest growth. The protein content of the powder were determined using the Kjelldahl method. Bangos powder from filleted fish had the highest protein content. Filleted and whole bangos powder fried at 79°C and 85°C were used in the formulation of the bouillon cubes. The two formulations consisted of varying percentages of bagnos powder combined with flour, cornstarch, MSG, salt and spices. Sensory evaluation of the dissolved bouillon cubes were conducted using trained panelists. The obtained results indicate that at the 5% level, panelists detected no difference between the two formulations. The panelists characterized the color of the bouillon cube as cream and grey which were not very acceptable. The appearance was ranked as slightly moist to loosely packed. General observation of the texture indicated that it was grainy. Flavor was characterized as slightly fishy. Microbial examination of the cubes showed an increase in growth after the addition of spices and other ingredients.